The Implementation of Right-Fulfillment to the Health Care in Achieving the Millennium Development Goal (MDG’S) - Muhammad Zuhri; Basri Basri (Hasanuddin Law Review, 2016)
The vision of Aceh Government in 2012-2017 is Aceh are dignified, prosperous, just, and independent based on the legislation of Aceh government as a form of Memorandum of Understanding. One of the visions of Aceh government 2012- 2017 is the improved welfare of Acehnese people through quality health services through increasing life expectancy, infant mortality, decreasing the prevalence of malnutrition as well as the effectiveness of the treatment of infectious diseases to the achievement of the MDG’s. Model policies adopted by the Aceh government is monitoring and track record of cases, tv monitor, routine and case sms, a special program policy model, and the model of budget balancing. Model policies adopted by the district/city government is making a supporting program, All Village Midwives Must Live in the Village, deliveries assistance is performed by professional health workers, adjustment to the ability of APBK. Support new regulation of Regent Regulation (Perbub) on Malaria Elimination and No Smoking Area. MDG’s target is not entirely in accordance with the indicator being built, because it requires adjustments in accordance with the ability of both district or city areas. Regulatory support is not adequate to support the achievement of the MDG’s in the field of health.